Integrative management model is a vector for improving customs authorities service activities - I. Yu. Sofiyannikova (Вестник университета)
The current problematic aspects of the functioning of the management model of the Russian Federation state bodies, based on the management principles, have been studied. The purpose of the study is to analyze the problem situations in the process of using the bureaucratic style of management based on hierarchical relations, as well as the advantages of the proposed integrative model. The relevance of the topic is conditioned by the necessity to improve the management system in customs authorities in order to improve the service environment and transition to a client-centered state. The main objectives of the research are to identify the shortcomings of the existing model of management in the state customs authorities, the interrelation of such shortcomings, and the process of rendering state customs services, as well as to propose possible options for their elimination. Both theoretical (analysis of the current legal and regulatory framework, as well as scientific works) and empirical (practical substantiation of the need to improve the functioning bureaucratic style of management in state customs authorities) methods of research were used. Based on the analysis of the existing model of management in the customs authorities system, the advantages and significant shortcomings have been revealed. The study results are the identification of issues in the functioning of the hierarchical management model, which has a negative impact on the activities in the state customs authorities services sphere, and the proposal to integrate the existing management model with the marketing model.